Electrospun Polyvinyl Alcohol/Sodium Alginate Nanocomposite Dressings Loaded with Zno and Bioglass: Characterization, Antibacterial Activity, and Cytocompatibility - Saavedra-Gonzalez, M (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Chronic wounds pose a great challenge due to their slow healing and susceptibility to infections, hence the need for innovative alternatives to conventional antibiotics, as increasing bacterial resistance limits the efficacy of current treatments. This paper addresses the development of novel electrospun membranes based on polyvinyl alcohol (PVA) and sodium alginate, incorporating therapeutic ZnO and bioglass (54SiO2:40CaO:6P2O5) nanoparticles. While nanocomposites presented smaller fiber diameters than pure polymers, ternary nanocomposites displayed higher values, e.g., in porous areas, values were in the ca. 80–240 nm range and 0.06–0.60 μm2, respectively. The Young’s modulus of the PVA/SA membrane, initially 15.9 ± 2.0 MPa, decreased by 65% with 10 wt.% ZnO NPs, whereas 10 wt.% BG NPs increased it by 100%. The membranes demonstrated efficacy against Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) isolated from a human wound secretion, as well as two ATCC strains: Staphylococcus aureus and Staphylococcus epidermidis. A cell viability assay conducted with HaCaT cells demonstrated nearly complete survival following 72 h of membrane exposure. Their combined Gram-positive antibacterial activity and cytocompatibility support their potential application as biofunctional dressings for the management of chronic and hospital-acquired topical infections, while also contributing to the global effort to combat antibiotic resistance. © 2025 by the authors.